CONFIDENHTTM SYSTEM SAFETY AND PERFORMANCE OF DIAGNOSTIC ELECTRICAL MAPPING OF RENAL NERVES FOR RENAL SYMPATHETIC DENERVATION PROCEDURE. (June 2018) - Tsioufis, K.; Mahfoud, F.; Kyriakos, D.; Feyz, L.; Kasiakogias, A.; Daemen, J.
Abstract : Objective: Renal denervation procedures remains a so-called blind procedure. The objective of the present study is to assess the safety and feasibility of renal nerve stimulation using the ConfidenHTTM mapping system. Figure. No caption available. Design and method: The Confiden(HT) study is a prospective first-in-man multicenter study designed to assess the safety and feasibility of renal nerve mapping using the ConfidenHT™ system in 20 hypertensive patients with an indication for coronary angiography or with a planned renal sympathetic denervation. The ConfidenHT™ System consists of two main parts, a catheter and a console. The Console delivers electrical energy to the catheter using a multi-channel stimulator, and a real time intra-arterial Blood Pressure (BP) monitor, which records, analyzes and displays the stimulation outcome (BP and/or HR changes) during stimulation. The ConfidenHT™ catheter is a non-occluding flexible catheter with expendable multi electrode design, compatible with an 8Fr guiding catheter and 0.014' guide wire, for a wide range of renal artery diameters. The technology could help to improve RDN procedures by providing: (1)better patient selection of RDN responders and non-responders, and (2)intra-procedural guidance and feedback to optimize technical success rates. The primary performance endpoint was the change in blood pressure during stimulation. 20 patients (58 ± 11.5 years old, 156 ± 23 office systolic BP, 9/11 male/female respectively, and GFR of 78 ± 13 mL/min/1.73 m2) have been included. Most of procedures were performed under local anesthesia with mild conscious sedation. Results: The system appeared safe in all 20 cases with no peri-procedural adverse events. Post stimulation there were no signs of angiographically visible spasms/thrombus or dissection in any of the treated arteries. A varying response to electrical stimulation was found among patients with a clear location dependent response along the artery (Hot and Cold spots). The increase in systolic BP and MAP ranged from 0 to 30 mmHg and 0 to 18 mmHg respectively. Conclusions: Results suggest that renal nerve mapping using the ConfidenHTTM system technology is feasible and safe and offers promising diagnostic electrical renal nerve mapping opportunities in hypertensive patients which could help in optimizing the result of renal sympathetic denervation.